2009
DOI: 10.1007/s11738-009-0353-9
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency adventitious shoots regeneration from leaf of non-heading Chinese cabbage (Brassica campestris ssp. chinensis) cultured in vitro

Abstract: The objective of the present work was selection of cultivar and suitable medium for regenerating shoots from leaf segments of non-heading Chinese cabbage. We evaluated six types of supplemented media with 2.0, 5.0 and 10.0 mg l -1 6-BA; 1.0 and 2.0 mg l -1 TDZ; 0.1, 0.3, 0.5, 0.8 and 1.0 mg l -1 NAA; 3.0, 5.0 and 7.5 mg l -1 AgNO 3 ; 0.01 mg l -1 2-4, D and 4.0 mg l -1 KT for shoot regeneration and six cultivars root formation three types of supplemented media with 0.2, 0.3, 0.5 mg l -1 NAA, and for survival r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It has also be found that addition of L-glutamine into the co-cultivation medium allowed the efficient Agrobacterium tumefaciens mediated transformation of tea by avoiding the bactericidal effect of leaf polyphenols produced by leaf tissues (Sandal et al, 2007). Addition of silver nitrate (AgNO 3 ), also known as an ethylene inhibitor, into the basal medium has significantly enhanced shoot production (Memon et al, 2009) and rooting (Dai et al, 2009); however, it has also been found that it can increase ethylene synthesis under in vitro cultures with several morphogenic responses but without basic molecular explanations (Zhang et al, 1998;Kumar et al, 2009).…”
Section: Stage I Introduction and Establishmentmentioning
confidence: 99%
“…It has also be found that addition of L-glutamine into the co-cultivation medium allowed the efficient Agrobacterium tumefaciens mediated transformation of tea by avoiding the bactericidal effect of leaf polyphenols produced by leaf tissues (Sandal et al, 2007). Addition of silver nitrate (AgNO 3 ), also known as an ethylene inhibitor, into the basal medium has significantly enhanced shoot production (Memon et al, 2009) and rooting (Dai et al, 2009); however, it has also been found that it can increase ethylene synthesis under in vitro cultures with several morphogenic responses but without basic molecular explanations (Zhang et al, 1998;Kumar et al, 2009).…”
Section: Stage I Introduction and Establishmentmentioning
confidence: 99%
“…The dose of cytokinin in the culture medium was sufficient to induce shoots in crambe, which is critical for effective organogenesis. The effect of BAP on the induction of multiple shoots has been previously reported in species of the family Brassicaceae (Shukla and Sawhney, 1991;Memon et al, 2009), but no studies have described the effect of this regulator over time in vitro cultures. Means followed by the same letter in the column do not differ by Tukey's test at 5% CV(%): percent coefficient of variation.…”
Section: Resultsmentioning
confidence: 98%
“…Means followed by the same lowercase letter in the columns do not differ by Tukey's test at 5%. Memon et al (2009) reported 90% rooting of Brassica campestris shoots in MS medium supplemented with 1 µM ANA, whereas only 54.4% rooting was observed when the medium was supplemented with 2.5 µM ANA. The results of Li et al (2010) using adventitious shoots generated from the hypocotyls of the C. abyssinica cultivar Galactica were not similar to those reported in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…BAP is one of the cytokinins with lowest cost, and has been very efficacious in the multiplication of diverse Brassicaceae species (Shukla and Sawhney, 1991;Memon et al, 2009;Ishigaki et al, 2009). Studies related to induction of shoots and regeneration of whole plants from apical segments have not yet been described for crambe.…”
Section: Shoot Multiplicationmentioning
confidence: 99%
“…For this, genetic transformation and in vitro culture techniques are important tools to be employed. However, the genetic transformation of plants demands the successful application of these techniques, requiring an efficient, viable, genetically loyal propagation system that provides plant material of good quality to satisfy this demand (Memon et al, 2009). …”
Section: Introductionmentioning
confidence: 99%